2012
DOI: 10.1167/iovs.12-9466
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Ophthalmic Artery Chemotherapy Triggers Vascular Toxicity through Endothelial Cell Inflammation and Leukostasis

Abstract: 1,6,9 PURPOSE. Super-selective intra-ophthalmic artery chemotherapy (SSIOAC) is an eye-targeted drug-delivery strategy to treat retinoblastoma, the most prevalent primary ocular malignancy in children. Unfortunately, recent clinical reports associate adverse vascular toxicities with SSIOAC using melphalan, the most commonly used chemotherapeutic. METHODS.To explore reasons for the unexpected vascular toxicities, we examined the effects of melphalan, as well as carboplatin (another chemotherapeutic used with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 22 publications
4
45
0
Order By: Relevance
“…Other subtle variations in the technique, such as the penetration of the microcatheter into the artery (1-2 cm reported in Muen et al (2012); just 1-2 mm into the ostium in our study) may explain some of the differences as well. Studies in vitro and in non-tumour bearing animals suggest that melphalan might be toxic to the retinal endothelial cells (Wilson et al 2011b;Steinle et al 2012). Histopathological findings indicative of vessel occlusion and intravascular foreign body reactions were found in enucleated eyes from IAM-treated patients both in our study and in a previous one (Eagle et al 2011).…”
Section: Discussionsupporting
confidence: 62%
“…Other subtle variations in the technique, such as the penetration of the microcatheter into the artery (1-2 cm reported in Muen et al (2012); just 1-2 mm into the ostium in our study) may explain some of the differences as well. Studies in vitro and in non-tumour bearing animals suggest that melphalan might be toxic to the retinal endothelial cells (Wilson et al 2011b;Steinle et al 2012). Histopathological findings indicative of vessel occlusion and intravascular foreign body reactions were found in enucleated eyes from IAM-treated patients both in our study and in a previous one (Eagle et al 2011).…”
Section: Discussionsupporting
confidence: 62%
“…However, the watershed zone can be vulnerable to ischemia, especially during times of severe systemic hypotension, because the most distal arteriolar branches have the lowest perfusion pressure [8]. The main choroidal watershed zone lies between the areas supplied by the medial and temporal PCAs, typically found on either side of or encompassing the optic disc and as a vertical strip superiorly and inferiorly to the optic disc [6, 9]. Here, we describe a unique case of choroidal ischemia secondary to IAC in which the watershed zone was spared.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in a nonhuman primate model revealed endothelial cell smudging, leukostasis, and terminal vascular occlusion following treatment with IAC using melphalan or carboplatin [9]. There is laboratory evidence that high doses of melphalan in vitro cause cell death in this manner, while low doses inhibit cell death [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vascular toxicity may be related to the pH, the pulsatile delivery or the chemotherapeutic drugs used 17. In a non-human primate model, the retinal arterioles revealed smudging of the endothelial cells and their basement membranes with terminal vessel occlusion 18.…”
Section: Discussionmentioning
confidence: 99%